1988
DOI: 10.1021/bi00420a020
|View full text |Cite
|
Sign up to set email alerts
|

4-Alkyl radical extrusion in the cytochrome P-450-catalyzed oxidation of 4-alkyl-1,4-dihydropyridines

Abstract: Rat liver microsomal cytochrome P-450 oxidizes the 4-methyl, 4-ethyl (DDEP), and 4-isopropyl derivatives of 3,5-bis(carbethoxy)-2,6-dimethyl-1,4-dihydropyridine to mixtures of the corresponding 4-alkyl and 4-dealkyl pyridines. A fraction of the total microsomal enzyme is destroyed in the process. The 4-dealkyl to 4-alkyl pyridine metabolite ratio, the extent of cytochrome P-450 destruction, and the rate of spin-trapped radical accumulation are correlated in a linear inverse manner with the homolytic or heterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…A plot of log (V,,,,,) for the P450 oxidation of substituted N,N-dimethylanilines versus Hammett 0 gives p = -0.6 (Burka et al 1985). 1,4-Dihydropyridine Hantzsch esters (August0 et al 1982, Lee et al 1988 and cyclopropylamines (Hanzlik 1979, Hanzlik and Tullman 1982, Macdonald et al 1982 are suicide inactivators of P450.…”
Section: Je-mentioning
confidence: 99%
See 2 more Smart Citations
“…A plot of log (V,,,,,) for the P450 oxidation of substituted N,N-dimethylanilines versus Hammett 0 gives p = -0.6 (Burka et al 1985). 1,4-Dihydropyridine Hantzsch esters (August0 et al 1982, Lee et al 1988 and cyclopropylamines (Hanzlik 1979, Hanzlik and Tullman 1982, Macdonald et al 1982 are suicide inactivators of P450.…”
Section: Je-mentioning
confidence: 99%
“…For example, the photochemical reaction of trans-stilbene with N-methyl-N-(trideuteriomethy1)-Ntert-butylamine, which was proposed to proceed via deprotonation of the N-methyl-N-(trideuteriomethy1)-N-tert-butylamine cation radical by the stilbene anion radical, gave an isotope effect of 2.2 (Lewis and Ho 1980). Other examples include the alkaline potassium ferricyanide oxidation of N-methyl-N,N-di-(n-buty1)amine versus N-(trideuteriomethy1)-N,N-di-(n-buty1)amine (kH/kD = 3.6) (Lindsay Smith and Mead 1973) and the electrooxidation of these amines in alkaline medium (&/AD = 2.9) (Lindsay Smith and Masheder 1976).…”
Section: Je-mentioning
confidence: 99%
See 1 more Smart Citation
“…However, such acute hepatic heme depletion was observed after treatment of rats with the P450 suicide inactivator 3,5-dicarbethoxy-2,6-dimethyl-4-ethyl-1,4-dihydropyridine (DDEP) Correia, 1983, 1985;Ren and Correia, 2000). DDEP irreversibly destroys the heme of hepatic P450s 2C11, 2C6, and 3A, but not CYP2B1 (Lee et al, 1988;Sugiyama et al, 1989). Such CYP2C11 and CYP2C6 destruction through heme pyrrole N-ethylation generates N-ethylprotoporphyrins, potent inhibitors of the terminal heme synthetic enzyme ferrochelatase.…”
mentioning
confidence: 99%
“…Therefore, it is assumed that the P450-catalyzed aromatization of the alkyltetrahydroquinolines undergoes an initial SET step to generate a radical nitrogen cation (II; Scheme 3). The postulation of the pathway from structure IV to structure VI (Scheme 3) was originated from the radical mechanism for the P450-catalyzed oxidation of 4-alkyl-1,4-dihydropyridine derivatives bearing various substitutions (Augusto et al, 1982;Böcker and Guengerich, 1986;Guengerich and Böcker, 1988;Lee et al, 1988). Augusto et al (1982) reported the radical mechanism for the oxidation of the dihydropyridines on the basis of spin-trapping of the alkyl radical released from the 4-position, and the mechanism was further supported by more evidence, e.g., no significant isotope effect for the 4-position hydrogen on the dehydrogenation (Guengerich and Böcker, 1988).…”
Section: Discussionmentioning
confidence: 99%